Detection of species-specific genetic markers in goat, sheep and pig by molecular characterization of Cytochrome b gene - RAJKHOWA, DEEKSHITA; KALITA, D J; BORAH, P; HUSSAIN, MD I; SAIKIA, D P; FERDOCI, A M (The Indian Journal of Animal Sciences, 2016)
Present work was designed to know the inter-species genetic variation by detecting polymorphisms and analysing the nucleotide sequences of cytochrome b gene. Blood samples were collected from apparently healthy adult animals of indigenous goat, sheep and pig of Asom, and mitochondrial DNA was extracted for amplification by PCR. One half of the PCR product was used for restriction digestion while the other half after purification was sent for sequencing. Species specific restriction patterns were observed for cytochrome b gene amplicon upon digestion with AluI, HinfI, and HaeIII. The nucleotide sequence results were further analyzed using ClustalW and Mega5 softwares for unambiguous species typing. The percent similarity study showed that goat cytochrome b gene had 89.64 and 82.12% similarity with sheep and pig respectively. Phylogenetic tree also revealed close relationship of goat and sheep cytochrome b gene. Lowest pair wise distance was observed between goat and sheep (0.123) followed by goat and pig (0.227). Pig and sheep cytochrome b gene showed the highest degree of pair wise distance (0.255) between the nucleotides. From the present study, it can be concluded that RFLP and sequence analysis of cytochrome b gene provided the information about the extent of inter-species genetic diversity and can be used as a powerful tool for genetic traceability of species.